Comparison of K-Means Clustering & Logistic Regression on University data to differentiate between Public and Private University - Adhien Kenya Anima Estetikha; Deden Hardan Gutama; Musthofa Galih Pradana; Dhina Puspasari Wijaya (International Journal of Informatics and Information Systems, 2021)
The development of advances in educational methods has developed in the last few decades. especially at the higher education level such as college. The rising interest of students in pursuing their higher education education has caused the sector to be split into two sectors, both private and public university. This difference raises several questions recently about how the two types differ in carrying out the educational process. whether there is a difference in terms of cost, service or quality, we really can't tell exactly. For this study, we will try to use the K-Means Clustering & Logistic Regression to group the University into two groups, Private and Public and then compare the two model accuracy. The results of this study show that the results obtained from the K-Means clustering model (22%) are much lower than the Logistic Regression model (91%).